Salivary Tick Cystatin OmC2 Targets Lysosomal Cathepsins S and C in Human Dendritic Cells - Zavašnik-Bergant, Tina; Vidmar, Robert; Sekirnik, Andreja; Fonović, Marko; Salát, Jiří; Grunclová, Lenka; Kopáček, Petr; Turk, Boris (Frontiers in Cellular and Infection Microbiology, 2017)
To ensure successful feeding tick saliva contains a number of inhibitory proteins that interfere with the host immune response and help to create a permissive environment for pathogen transmission. Among the potential targets of the salivary cystatins are two host cysteine proteases, cathepsin S, which is essential for antigen- and invariant chain-processing, and cathepsin C (dipeptidyl peptidase 1, DPP1), which plays a critical role in processing and activation of the granule serine proteases. Here, the effect of salivary cystatin OmC2 from Ornithodoros moubata was studied using differentiated MUTZ-3 cells as a model of immature dendritic cells of the host skin. Following internalization, cystatin OmC2 was initially found to inhibit the activity of several cysteine cathepsins, as indicated by the decreased rates of degradation of fluorogenic peptide substrates. To identify targets, affinity chromatography was used to isolate His-tagged cystatin OmC2 together with the bound proteins from MUTZ-3 cells. Cathepsins S and C were identified in these complexes by mass spectrometry and confirmed by immunoblotting. Furthermore, reduced increase in the surface expression of MHC II and CD86, which are associated with the maturation of dendritic cells, was observed. In contrast, human inhibitor cystatin C, which is normally expressed and secreted by dendritic cells, did not affect the expression of CD86. It is proposed that internalization of salivary cystatin OmC2 by the host dendritic cells targets cathepsins S and C, thereby affecting their maturation.